ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI CABAI RAWIT PADA MUSIM PENGHUJAN DI KOTA MATARAM - Cornelius Sopar Nababan; Asri Hidayati; Muhammad Nursan (Fakultas Pertanian Universitas Mataram, 2022)
Chilli pepper is a very important commodity to be developed because it has high economic value. The price of chilli pepper is also high, especially during the rainy season. This study aims to: (1) analyze the costs and income of chilli pepper farming during the rainy season in the city of Mataram; (2) analyzing the feasibility of chilli pepper farming in the rainy season in Mataram City; (3) analyzing the constraints faced by farmers in conducting chilli pepper farming during the rainy season in the city of Mataram. The method used is descriptive method and data collection is done by survey techniques. The research respondents were 30 people who were taken by proportional sampling. The data collected was then analyzed descriptively. The results showed that: (1) The average production cost of chilli pepper farming during the rainy season in Mataram City was IDR 8,731,397.82 per cultivated land area per planting season or IDR 72,761,648.50 per hectare per planting season and the average -the average income of chilli pepper farming during the rainy season in Mataram City is IDR 17,095,113.19 per cultivated land area per planting season or IDR 142,459,284.50 per hectare per planting season; (2) The value of the R/C ratio and B/C ratio of chilli pepper farming in the rainy season in Mataram City is 2.95 and 1.95 so that chilli pepper farming in the rainy season in Mataram City is feasible to cultivate; (3) the obstacles faced by farmers in conducting chilli pepper farming during the rainy season in the city of Mataram include bacterial wilt disease, fruit rot disease and stunted plants.